Public Relations Management of National Identity in International Exhibitions: An Analytical Study of the Expo 2020 Instagram Page - Muhammad, Arrak Ghanem; Saleh, Elaf Mahdi (ALBAHITH ALALAMI, 2024)
The research aims to study how public relations (PR) departments capitalize on international events to manage and market a country’s national identity through digital media platforms. The researchers analyzed the official Instagram page for Expo 2020, utilizing a survey method and qualitative content analysis tool. They employed comprehensive enumeration to analyze the posts related to the national symbols of the UAE, amounting to 862 posts. The research concluded with several key findings, the most important of which is that the PR management focused on the national philosophy of the state through the iconic visual logo. They relied on a collection of cultural, political, historical, geographical, and military symbols to manage the national identity. Great care was taken to include a broad range of symbols to provide a comprehensive representation of the country’s rich historical heritage. The study also recommended that the study of national identity should be given more space in academic research to yield precise results that offer a deeper understanding of the role of public relations in marketing national identity. This is because identity is considered the first stage in the process of building a nation’s reputation.